Taxonomic revision of the dolphin genus Lagenorhynchus. Issue 3 (31st January 2019) - Vollmer, Nicole L.; Ashe, Erin; Brownell, Robert L.; Cipriano, Frank; Mead, James G.; Reeves, Randall R.; Soldevilla, Melissa S.; Williams, Rob
Abstract: Evolutionary relationships among cetaceans within the family Delphinidae have been difficult to resolve due to the high number of species and their relatively rapid radiation. This is the case for the dolphin species currently placed in the genus Lagenorhynchus, and their relations to Cephalorhynchus and Lissodelphis species. Phylogenetic relationships among these species have been investigated using multiple lines of evidence, and that evidence consistently suggests that the six species currently assigned to Lagenorhynchus do not form a monophyletic group. Here, we summarize findings from studies of morphology, genetics, historical biogeography, and acoustics that offer insight into the phylogenetics of these taxa. We present the taxonomic basis for revision of Lagenorhynchus, propose retention of Lagenorhynchus albirostris and reassignment of the remaining five species into other existing generic names, namely Leucopleurus acutus, Sagmatias australis, Sagmatias cruciger, Sagmatias obliquidens, and Sagmatias obscurus . Making these revisions now so that the taxonomy better reflects evolutionary relationships among these species will ensure that future studies include the most appropriate taxa for investigating the complex phylogenetic and systematic relationships among cetaceans. However, comprehensive analyses using multiple lines of evidence are still needed to clarify the phylogenetic relationships within and among the Lissodelphininae genera Cephalorhynchus, Lissodelphis, and Sagmatias .